Marketing: Farmers Promulgates Cash Crops, Itinerary to Support Their Livelihood and Enhance Their Living Standard - Onessimos Shangdiar (Research Synergy Foundation, 2021)
This paper is a briefing on the marketing and emergence of cash crops in the Indo-Bangladesh border, South West Khasi Hills District Meghalaya. It is solely aimed at understanding the inborn entrepreneurship skills of the particular sub-tribe of the Khasis called